2021
DOI: 10.21037/jtd-20-3039
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of non-intubated video-assisted thoracic surgery with spontaneous ventilation and intubated video-assisted thoracic surgery: a meta-analysis based on 14 randomized controlled trials

Abstract: Background: Video-assisted thoracic surgery (VATS) generally involves endotracheal intubation under general anesthesia. However, inevitably, this may cause intubation-related complications and prolong the postoperative recovery process. Gradually, non-intubated video-assisted thoracic surgery (NIVATS) is increasingly being utilized. However, its safety and efficacy remain controversial.Methods: Randomized controlled trials (RCTs) published up to August 2020 were selected from the Cochrane Library, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…Wen et al conducted a meta-analysis of 27 studies on SV-VATS and concluded that the advantages of SV-VATS in reducing postoperative complications and accelerating postoperative recovery compared to traditional MV-VATS (11). A meta-analysis of 14 RCTs of two VATS modes reported that SV-VATS reduced postoperative hospital stay and patients' subjective discomfort after surgery (12). A meta-analysis involving more than 1,600 patients reached similar conclusions (13).…”
Section: Discussionmentioning
confidence: 97%
“…Wen et al conducted a meta-analysis of 27 studies on SV-VATS and concluded that the advantages of SV-VATS in reducing postoperative complications and accelerating postoperative recovery compared to traditional MV-VATS (11). A meta-analysis of 14 RCTs of two VATS modes reported that SV-VATS reduced postoperative hospital stay and patients' subjective discomfort after surgery (12). A meta-analysis involving more than 1,600 patients reached similar conclusions (13).…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis by Zhang et al based on 14 RCTs, also reported technical outcomes, such as surgical field satisfaction (SFS), and anaesthesia satisfaction scores (ASC). SFS was measured on a scale from 1-4 (1: best vision and lung collapse; and 4: worst exposure to the surgical field and the need to convert to intubation), and did not confirm significant difference in NI-VATS vs. I-VATS, however ASC proved to be significantly higher in cases of NI-VATS (35). With the spread of NI-VATS, the importance of careful patient selection also needs to be addressed.…”
Section: Anaesthesia For Ni-vats and I-vatsmentioning
confidence: 97%
“…Results have also shown that overall complication rate was lower in NI-VATS [odds ratio (OR) 0.41; 95% CI: 0.25 to 0.67; P=0.0004], with decreased incidence of air-leaks (OR 0.45; 95% CI: 0.24 to 0.87; P=0.02) and postoperative hoarseness (OR 0.06; 95% CI: 0.02 to 0.21; P<0.00001) (35).…”
Section: Anaesthesia For Ni-vats and I-vatsmentioning
confidence: 99%
“…Relative contraindications include hemodynamic instability, obesity with body mass index (BMI) greater than 30, high airway secretions, coagulopathy, and extensive adhesions from prior surgery leading to surgical difficulty (33). Patients can be maintained as spontaneously breathing from the beginning or return to spontaneously breathing before the airway is open (35)(36)(37).…”
Section: Nonintubated Spontaneous Breathingmentioning
confidence: 99%